Evaluation of impulse oscillometry in pigs originating from the field - Püllen, Cilia; Justus Liebig University Giessen (My University, 2015)
For the first time, the applicability of the impulse oscillometry system (IOS) was assessed for lung function analysis in pigs originating from the field. Fifty-eight German hybrid pigs from 29 different herds were chosen in pairs from one pen, each for routine diagnostics in the context of herd health service. The pigs were brought to the Clinic for Swine of the Justus-Liebig-University Giessen and examined according to standard clinical methods. Routine clinical examination was extended to a total set of 29 parameters, representing detailed clinical signs of the respiratory system. The overall examination was complemented by impulse oscillometry, bronchoalveolar lavage (BAL) and detailed pathology. Bronchoalveolar lavage fluid (BALF) and lung tissue samples were examined for relevant airway pathogens in swine using molecular and microbiological methods. In addition, BALF was examined by differential cytology.The present study focused on the methodological aspects and sensitivity of IOS to variations in pulmonary mechanics as well as on the relationship between clinical findings and the results of lung function analysis.The variability of repeated IOS runs increased significantly after the sixth run. Therefore, the average of the first six runs for each individual pig was used for further analysis. High repeatability and the pronounced interindividual variability of test results suggested impulse oscillometry as a potential method for improving clinical diagnostics in pigs with respect to respiratory diseases.Eight clinical parameters exhibiting a marked relationship with the results of impulse oscillometry were extracted via multiple regression analysis. The resulting linear relationship between the clinical data and IOS parameters had a mean r2 of 0.52. Correlations between clinical data and IOS parameters were statistically significant, particularly for disturbances in the lower respiratory tract. The correlations between clinical findings and the reactance area (AX) were similar to established IOS parameters, indicating the ability of AX to qualitatively and quantitatively assess functional disorders in the lung periphery.Because of the limited relationship between pulmonary functional disorders and clinical data, the inclusion of the additional diagnostic methods, especially pathological and histological examination, is expected to detect further factors, leading to the high variability impulse oscillometric results. Based on the present findings, IOS can be applied in conjunction with routine diagnostic methods as a valuable non-invasive technique, providing complementary information for the detection and quantification of functional respiratory impairments in pigs originating from the field.

In dieser Studie wurde die Anwendbarkeit der Impuls-Oszilloresistometrie erstmals als Methode zur Lungenfunktionsuntersuchung bei Schweinen aus dem Feld überprüft. 58 deutsche Hybridschweine aus 29 verschiedenen Herden wurden zu jeweils zwei Tieren aus einer Bucht für die Routinediagnostik im Rahmen des Gesundheitsmonitorings ausgewählt. Die Tiere wurden an die Klinik für Schweine der Justus-Liebig-Universität Giessen verbracht und dort mittels klinischer Standardmethoden untersucht. Die klinische Routineuntersuchung wurde um 29 Parameter erweitert, welche detaillierte respiratorische Krankheitsanzeichen repräsentierten. Die Gesamtuntersuchung wurde durch das Impuls-Oszilloresistometrie-System (IOS), der bronchoalveolären Lavage und einer ausführlichen pathologischen Untersuchung ergänzt. Bronchoalveoläre Lavageflüssigkeit (BALF) und Lungengewebe wurden mittels molekularen und mikrobiologischen Untersuchungsmethoden auf relevante Atemwegserreger des Schweins untersucht. Eine Differentialzytologie der BALF wurde ebenfalls durchgeführt.Die Schwerpunkte der vorliegenden Untersuchung waren die Beurteilung der methodischen Aspekte und Sensitivität des IOS sowie die Bewertung des Bezugs zwischen klinischen Befunden und Ergebnissen der Lungenfunktionsanalyse.Die Variabilität der wiederholten Lungenfunktionsmessungen stieg nach dem sechsten Messdurchgang signifikant an. Daher wurden die ersten sechs Messdurchgänge jedes Schweins für die weiteren Auswertungen gemittelt. Eine hohe Wiederholbarkeit sowie eine ausgeprägte interindividuelle Variabilität der Messergebnisse deuteten auf das Potenzial der Impuls-Oszilloresistometrie hin, klinische Diagnostikmethoden in Bezug auf porzine respiratorische Erkrankungen mit dieser neuen Methode optimieren zu können.Mittels multipler Regressionsanalyse konnten acht klinische Parameter, die einen ausgeprägten Bezug zu IOS Daten aufweisen, extrahiert werden. Die lineare Beziehung zwischen klinischen Daten und Parametern der Atemmechanik wies ein mittleres Bestimmtheitsmaß (r2) von 0,52 auf. Klinische Daten, die den unteren Atemtrakt reflektieren, korrelieren eng mit den bestehenden Parametern der Impuls-Oszilloresistometrie, welche die Lungenperipherie darstellen. Die Korrelationen zwischen klinischen Befunden und der Reactance-Fläche (AX) glichen denen gängiger IOS Parametern. Dies deutete auf das Potenzial von AX hin, Veränderungen in der Lungenperipherie qualitativ und quantitativ darstellen zu können.Der Bezug zwischen pulmonalen Funktionsstörungen und klinischen Daten war begrenzt. Durch Einbeziehung weiterer diagnostischer Methoden im Gesamtprojekt, vor allem der pathologischen Anatomie und Histologie ist zu erwarten, dass weitere Faktoren ermittelt werden können, die zu der hohen Variabilität der IOS Ergebnisse geführt haben.Anhand der vorliegenden Ergebnisse bietet sich die Impuls-Oszilloresistometrie in Verbindung mit Methoden der Routinediagnostik als nützliches nicht-invasives Verfahren an, ergänzende Information zur Erkennung und Quantifizierung von funktionellen respiratorischen Störungen in Schweinen aus dem Feld zu liefern.
Keywords: ddc:630